Integrated Ising model with global inhibition for decision-making - Olga Tapinova; Tal Finkelman; Tamar Reitich-Stolero; Rony Paz; Assaf Tal; Nir S. Gov (Proceedings of the National Academy of Sciences, 2025)
Humans and other organisms make decisions choosing between different options, with the aim of maximizing the reward and minimizing the cost. The main theoretical framework for modeling the decision-making process has been based on the highly successful drift-diffusion model, which is a simple tool for explaining many aspects of this process. However, recent observations challenge this model. It was found that inhibitory tone increases during situations of difficult discrimination tasks, but the origin of this phenomenon is not understood. Motivated by this observation, we extend a recently developed model for directional decision-making of animals moving in real space. We introduce an integrated Ising-type model that includes global inhibition and use it to describe two-choice decision-making. This model can explain how the brain may utilize inhibition to improve its decision-making accuracy. Compared to experimental results, this model suggests that the regime of the brain’s decision-making activity is in proximity to a critical transition line between the ordered and disordered phases. Within the model, this observation can be explained by noting that this critical region has unique dynamics that give rise to advantageous properties for the decision-making process.